Sustainable quality management of landscapes: Visions, strategies and instruments to develop a regenerative and creative landscape according to a landscape-(thermo-)dynamic perspective - Brüll, Anja; Bürgow, Grit; Küddelsmann, Ina (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Concerning the question which requirements future landscapes will have to fulfil, basic landscape functions such as regenerating a moderate climate, clear water, fertile soil etc. are to be emphasized to be the essential „wing-unit” of society. An understanding of the interactions of the energy, water and material flows within the landscape thereby can serve as a system — oriented planning and design tool. The concept of a „Sustainable Quality Management of Landscape” based on a model of landscape dynamics offers an integrative field of action for spatial planning to be performed in water catchment areas.